2020
DOI: 10.1080/20008198.2020.1729033
|View full text |Cite
|
Sign up to set email alerts
|

Exploring cultural differences in the use of emotion regulation strategies in posttraumatic stress disorder

Abstract: Background: Emotion regulation difficulties are central to posttraumatic stress disorder (PTSD). While cultural differences exist in the ways in which individuals regulate their emotions, researchers have not examined cultural differences in emotion regulation in PTSD. Objective: This study explored emotion regulation in individuals from European and East Asian cultures with and without PTSD. Method: Emotion regulation measures were administered to Caucasian Australian (n = 31) and East Asian Australian (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
(36 reference statements)
2
21
0
Order By: Relevance
“…Another of social-emotional processes [ 29 ], which may lead to PTSD symptoms. For example, both cultural differences in relation to emotional dysregulation and associated PTSD symptoms [ 30 ], as well as in neural correlates of affective and cognitive functions that impact on the subsequent manifestation and progression of PTSD [ 31 ], have been found.…”
Section: Discussionmentioning
confidence: 99%
“…Another of social-emotional processes [ 29 ], which may lead to PTSD symptoms. For example, both cultural differences in relation to emotional dysregulation and associated PTSD symptoms [ 30 ], as well as in neural correlates of affective and cognitive functions that impact on the subsequent manifestation and progression of PTSD [ 31 ], have been found.…”
Section: Discussionmentioning
confidence: 99%
“…European Australian trauma survivors with PTSD have been found to report less use of individualistic reappraisal strategies, and greater use of suppression, worry, and emotion dysregulation than European Australian trauma survivors without PTSD. For Asian Australian trauma survivors these regulation strategies were not associated with PTSD symptoms [22]. It has recently been proposed that Asian cultures that value interdependence may find interpersonal emotion regulation strategies to be particularly effective in reducing negative affect [23].…”
Section: Introductionmentioning
confidence: 94%
“…However, these studies have all been conducted using Asian samples living in Western cultures, which raises questions about acculturation and generalizability to Asian cultures. Moreover, much of this research has demonstrated that Western-focused appraisals and emotion regulation strategies have less relevance for trauma survivors from Asian cultural backgrounds, e.g., [19][20][21][22]. Thus, important questions still remain regarding what appraisals and emotion regulation strategies are of relevance for trauma survivors with PTSD from Asian cultural backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that greater use of suppression and lower use of reappraisal is related to greater PTSS [ 12 , 21 23 ]. However, perceived benefits or consequences of emotion regulation strategies vary depending on context and cultural expectations [ 10 , 20 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%